Influence of immune cells and inflammatory factors on Alzheimer’s disease axis: evidence from mediation Mendelian randomization study - Linzhu; Jianxin Zhang; Wenhui Fan; Chen Su; Zhi Jin (BMC Neurology)
Abstract Background Alzheimer’s disease (AD) is one of the most common forms of dementia in the elderly, characterized by progressive neurodegeneration. While the exact etiology of AD remains unclear, immune inflammation is known to play a significant role in the disease. Methods This study utilized a two-sample Mendelian randomization (MR) approach to assess the causal relationship between different types of immune cells and AD, while considering inflammatory factors as intermediate variables. Data were collected from three sources: immune cell data (731 phenotypes), inflammatory factors (48 cytokines from 8,293 individuals), and AD data (35,274 cases, 59,163 controls). Multiple MR methods were employed to minimize bias, and detailed descriptions of instrumental variable selection and statistical methods were provided. Results The study findings suggest potential causal relationships between six different types of immune cells and AD, as well as causal relationships between 13 immune cells and inflammatory factors. Additionally, two statistically significant inflammatory factors were found to have potential causal relationships with AD. Specifically, immune cells CD33-HLA DR + and CD45 on CD33-HLA DR + may further influence AD by regulating Interleukin-2 levels. Conclusion This study provides valuable insights into the immunoinflammatory pathogenesis of AD and offers partial guidance for the development of relevant interventions, thereby contributing beneficial information for the prevention and treatment of related diseases.